And then they stopped talking to me : making sense of middle school - Warner, Judith, 1965- (Crown, 2021)
"The French have a name for the uniquely hellish years between elementary school and high school: "l'âge ingrat" or "The Ugly Age." Characterized by a perfect storm of developmental changes-physical, psychological, and social-the middle-school years are a time of great distress for parents and children alike, marked by hurt, isolation, exclusion, competition, anxiety, and often outright cruelty. Some of this is inevitable; there are intrinsic challenges to early adolescence. But these years are harder than they need to be, and Judith Warner believes that adults are complicit. With piercing insight, compassion, and humor, Warner walks us through a new understanding of the role that middle school plays in all our lives. Part intellectual investigation and part call to action, this timely book unpacks one of life's most formative periods and shows how we can help our children not only survive it, but thrive"--